Designing An Investment Learning App for Students Using Design Thinking Approach - Yulius, Rina; Nasrullah, Muchamad Fajri Amirul; Handayani, Siskha; Thohari, Ahmad Hamim (Universitas Trilogi, 2023)
Young people's awareness of stock investment is still low. Lack of knowledge about the investment stock market is an example of financial literacy. Moreover, the development of financial applications with game elements has created a new trend in the investment field. Therefore, we proposed a playful application as a learning medium to improve young people's stock market investment knowledge. This research aims to develop a mobile his application that can be used to improve the financial literacy, especially investment literacy, of Politeknik Negeri Batam students. The study uses a design thinking approach and leverages gamification to increase user retention. A total of 50 participants contributed to this study. Tracking, observing, and identifying problems that exist in the spread of financial literacy practices among Politeknik Negeri Batam students allows us to find new ideas as solutions to existing problems. The trial conducted on the product revealed that while users found the application overall useful and aligned with their requirements, there are still areas that need improvement.